Irrigated vegetable farming in urban Ghana: a farming system between challenges and resilience - Drechsel, Pay; Adam-Bradford, A.; Raschid-Sally, Liqa (2014)
This chapter serves as an introduction to the book and provides brief information about urbanization in West Africa, and in Ghana in particular, the general role of urban agriculture and the common use of polluted irrigation water. It describes our focus on irrigated smallholder vegetable production and our understanding of the terms ‘urban‘, ‘peri-urban’ and ‘wastewater’. The chapter reflects on some of the key challenges of the farming system, its dynamic and resilience. It also gives an overview on the structure of the book, the origins of the data and the main objective of this publication.